Outcomes Associated With a Five-Point Surgical Site Infection Prevention Bundle in Women Undergoing Surgery for Ovarian Cancer. Issue 4 (October 2017) - Lippitt, Melissa H.; Fairbairn, Melissa Gerardi; Matsuno, Rayna; Stone, Rebecca L.; Tanner, Edward J.; Wick, Elizabeth C.; Angarita, Ana C.; Roche, Kara Long; Levinson, Kimberly L.; Bergstrom, Jennifer E.; Sinno, Abdulrahman K.; Curless, Melanie S.; et al.
Abstract : OBJECTIVE: To identify risk factors for surgical site infection and to define rates associated with cytoreductive surgery before and after implementation of an infection prevention bundle. METHODS: We conducted a prospective quality improvement study. Patients who underwent ovarian, fallopian tube, or peritoneal cancer cytoreductive surgery at an academic tertiary care center from April 2014 to April 2016 were prospectively enrolled. Patient demographics, surgical variables, and surgical site infection rates were compared with a historical cohort after introduction of a 5-point infection prevention bundle, including: 1) preoperative and intraoperative skin preparation with 4% chlorhexidine and intraoperative vaginal preparation with 4% chlorhexidine; 2) preoperative use of oral antibiotics and mechanical bowel preparation; 3) appropriate timing of intraoperative antibiotics; 4) adoption of enhanced sterile surgical techniques for colon procedures and incisional closure; and 5) perioperative incision management. RESULTS: During the study period, 219 women underwent surgery: 91 prebundle and 128 treated in the postbundle period. Stage, body mass index, proportion of patients undergoing colon or upper abdominal surgery, and estimated blood loss were not different between the cohorts. Overall, the surgical site infection rate prebundle was 18 (20%); this was reduced to four (3%) postbundle (odds ratio [OR] 0.13, 95% CI 0.037–0.53; P <.001). Patients who underwent a colon resection prebundle had an infection rate of 14 (33%) compared with three (7%) in the postbundle group (OR 0.14, 95% CI 0.037–0.53; P <.001). Additionally, rates of surgical site infection–related hospital readmission were also lower in the postbundle (4/128 [3%]) compared with the prebundle group (12/91 [13%]; P =.005). CONCLUSION: Infection is common after ovarian cancer cytoreductive surgery. Implementation of a 5-point surgical site infection prevention bundle in women undergoing ovarian cancer operations was associated with dramatically decreased infection rates and lower hospital readmission rates. Abstract : Implementation of an infection prevention bundle in women undergoing ovarian cancer surgery is associated with decreased infection rates.